“Presented by Lady Simpson:” An herbarium of wildflowers from Red River (1830-1833) - Beauregard, Frieda; Novicoff, Mallory (Scientia Canadensis, 2024)
Dried plant collections hold significant value as records of past ecosystems and cultures. Here, we introduce to public knowledge a small personal herbarium made by Frances Simpson, spouse of Sir George Simpson. It is one of few collections from early nineteenth century Rupert’s Land and the only one known made by a woman. The specimens include many notes, evidence of Simpson’s botanical knowledge, the floras she consulted, and her thoughts on aesthetics. We include excerpts from a discussion we held at the Manitoba Museum with three Métis botanical knowledge keepers regarding this collection’s significance and the many possible directions for its use.